Exposure time and different concentrations of GA3 in germination of seeds of Corymbia citriodora Hill & Johnson (Myrtaceae) - Souza-Leal, Thiago de [UNESP]; Silva, Isa Mara da; Martine, Gisela de Assis; Pessa, Henderson; Pedroso-de-Moraes, Cristiano (Fundacao Zoobotanica Rio Grande Sul, Museu Ciencias Naturais, 2019)
The germination of Corymbia citriodora was evaluated in five periods of exposure under different concentrations of GA3. The treatments were: distilled water and gibberellic acid at 5, 10 and 20 mg L-1, added to four batches of 100 seeds each. Soaking was carried out in periods of 30, 60, 120 and 180 min. The obtained data were used to calculate the Germinability (G%), Germination Speed Index (GSI) and Average Germination Time (AGT). The analysis of the results show that, compared to G%, the best averages were obtained for the interaction occurred by exposure of seeds for 30 minutes at a concentration of 20 mg L-1 GA3. With respect to the GSI, the best interaction occurred between the concentration of 5 mg L-1 GA3 in 120 minutes of exposure. For AGT, the best interaction occurred between the concentration of 5 mg L-1 GA330 minutes of exposure.
Keywords: eucalyptus; plant regulator; plant production